O Programa de Aceleração do Crescimento no Maranhão: uma análise de sua função como indutor do crescimento econômico - SILVA, Adriana Cristina Rabelo da (2014)
The Brazilian State has assumed distinct roles throughout its historic process, passing through a period of greater intervention in economic activity (National Developmentalism), to one in which its action is restricted to the minimum functions (neoliberalism). Currently, in the context of the neoliberal strategy crisis was launched the Growth Acceleration Program (in Portuguese, PAC) being characterized by a set of economic policies oriented to making investments in infrastructure and institutional actions. With the Keynesian view that economic growth depends on execution of investments, this work aims to investigate the extent of which PAC investments contributed to economic growth of Maranhão State, between 2007 and 2011. In order to explain the results obtained, this work initially presents the main economic planning strategies adopted in modern period of brazilian economic. Then a PAC characterization is presented, as well as some expositions of its evaluations and results. Lastly, this work focuses its analysis to PAC actions in Maranhão State, evidencing its financial execution during the period and its possible contribution to GDP Gross Domestic Product, in Portuguese, PIB). Finally, it was noted that, possibly, the PAC contribution to economic growth assumed a residual carater